Changes in the structures of U.S. companies: Action implications for executives and researchers - George P. Huber (Journal of Organization Design, 2016)
I draw primarily on two recent works to describe recent and ongoing changes in the business environment and in the structure of U.S. companies. Based on these changes, I describe what I see as action implications for executives and scientists, especially organization scientists. The first-described of the two works focuses on what today's large, traditionally structured companies must do to remain competitive in the changing business environment. The second work focuses on the proliferation of non-traditionally structured companies and on the effects of these companies on the more traditionally structured companies, and on society. My motivations for suggesting certain action implications for executives and scientists are two. One is that, as I will explain in some detail, some of these changes in the business environment are dangerous to businesses. The other is that a particular to-be-described change in the mix of structures of U.S. companies has seriously adverse effects on U.S. society.
Keywords: 650; Environmental change; Organizational change and redesign; New organizational forms; Societal changes; Recommended executive actions; Recommended research directions